La adopción en parejas menores de 25 años - Marín Iñiguez, Marcia Paulina (2018)
The article 159 of the code of childhood and adolescence Ecuadorian establishes as one of the requirements for the adoptive parents candidates:... "4. Be over twenty-five years". Since time immemorial the States were concerned about the rights of the child considered the present and the future of a company, being a very important legal institution of the right of children and the family law. It is for this reason, that has been created as na solution, although not entirely satisfactory, the institution of adoption of minors and adolescents, fact that goes back to times even before the Christian era. But this legal institution has its limitations by age, since establishing that only children under eighteen years of age and may be adopted by exception under twenty-one years of age persons. Beyond this age is prohibited any kind of adoption; and also in article 159, paragraph 4, is designated as a requirement that couples that will take over 25 years. However when in article 163, the banned adoptions do not consist that occur between people in which the adopter is less than twenty-five years, so according to a legal adage, in civil and public law "everything that the law does not prohibit, permitting" There are writers who established as biological age and above all psychological ideal to conceive a baby between the 24 years old and 34 years of age in women and 25 years of age and 35 years in the male, based its criteria the evolving physical and psychic people both men and women. But in the current reality, there are men and women who before this age have become fathers and mothers, while it restricts the responsibility have exercised and exercise against their children. It is common at this time to see how fifteen-year-old women, more or less, are pregnant or have already lighting to your child, without that is why they have become irresponsible people of his paternity or maternity. The Constitution of the Republic establishes the eighteen years of age so that people assume rights and extent of obligations and adopting a minor, is a serious responsibility and obligation, so that there is a legal contradiction in these principles. In Ecuadorian legislation for minors, with regard to the age, does not prohibit the adoption of a minor by a person that has less than twenty-five years of age, can do so, but according to the Art, 159 of the code on children and adolescents, located as a requirement, only, which is the old for what should be an amendment to paragraph 4 of that article, changing to "be more than twenty-five years" by "to be more than eighteen years", as indicated, the age is not necessarily synonymous with responsibility.